2019
DOI: 10.1021/acs.organomet.9b00131
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Free Well-Defined Mn(I) Complex-Catalyzed Synthesis of Amine, Imine, and 2,3-Dihydro-1H-perimidine via Hydrogen Autotransfer or Acceptorless Dehydrogenative Coupling of Amine and Alcohol

Abstract: The application of nontoxic, earth-abundant transition metals in place of costly noble metals is a paramount goal in catalysis and is especially interesting if the air-and moisture-stable ligand scaffold is used. Herein, we report the synthesis of amines/imines directly from alcohol and amines via hydrogen autotransfer or acceptorless dehydrogenation catalyzed by welldefined phosphine-free Mn complexes. Both imines and amines can be obtained from the same set of alcohols and amines using the same catalyst, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 114 publications
1
59
0
Order By: Relevance
“…The catalytic ability of a manganese‐NNS pincer complex 123 was demonstrated in the synthesis of imines, amines and 2,3‐dihydro‐1 H‐ perimidines by Srimani et al. through dehydrogenative coupling of alcohols and amines (Scheme ) . This was found to be the first phosphine‐free Mn‐pincer protocol that could be used for the synthesis of secondary amine as well as imine from the same alcohol and primary amine by varying the base.…”
Section: Synthesis Of Imines and Aminesmentioning
confidence: 98%
See 1 more Smart Citation
“…The catalytic ability of a manganese‐NNS pincer complex 123 was demonstrated in the synthesis of imines, amines and 2,3‐dihydro‐1 H‐ perimidines by Srimani et al. through dehydrogenative coupling of alcohols and amines (Scheme ) . This was found to be the first phosphine‐free Mn‐pincer protocol that could be used for the synthesis of secondary amine as well as imine from the same alcohol and primary amine by varying the base.…”
Section: Synthesis Of Imines and Aminesmentioning
confidence: 98%
“…2,3‐Dihydro‐1 H ‐perimidines were synthesised using a manganese‐NNS pincer‐catalysed dehydrogenative coupling strategy by Srimani et al. (Scheme ) . The coupling of various alcohols occurred with 1,8‐diaminonaphthalene by using 5 mol% of 123 along with a catalytic amount of KOH in toluene at 140 °C for 24–72 h. Substrate scope analysis reveals that the reaction provides moderate to good yields for aromatic alcohols and poor yields for aliphatic alcohols.…”
Section: Synthesis and Derivatisation Of Heterocyclic Compoundsmentioning
confidence: 99%
“…It was found that a potassium base favored the alkylation of amines, whereas imine formation was observed when a sodium base was used (Scheme c) . Recently, Srivastava, Srimani, and co‐workers have disclosed a phosphine‐free manganese complex Mn‐4 for the same reaction (Scheme d) . Madsen and co‐workers have developed high valent salen manganese(III)‐complex Mn‐5 and porphyrin Mn(III)‐complex Mn‐6 for the synthesis of imines via the ADC of alcohols with amines (Scheme e,f)…”
Section: Carbon‐heteroatom Bond Formationmentioning
confidence: 99%
“…[17] Recently, Srivastava, Srimani, and co-workers have disclosed a phosphine-free manganese complex Mn-4 for the same reaction (Scheme 4d). [18] Madsen and co-workers have developed high valent salen manganese(III)-complex Mn-5 and porphyrin Mn(III)-complex Mn-6 for the synthesis of imines via the ADC of alcohols with amines (Scheme 4e,f). [19]…”
Section: Adc Of Alcohols With Aminesmentioning
confidence: 99%
See 1 more Smart Citation